2023
DOI: 10.55591/001c.74170
|View full text |Cite
|
Sign up to set email alerts
|

Child Life Internship Readiness: Perspectives of Child Life Training Coordinators and Supervisors

Abstract: Certified Child Life Specialists serve an important role in the pediatric healthcare system providing psychosocial care for children and their families. While the child life profession continues to grow, the student-to-professional pipeline has not been researched. This mixed-methods study focuses on internship readiness from the clinical internship coordinators’ and supervisors’ perspectives to understand the child life intern selection process. Results indicate there are criteria that qualify and disqualify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…Furthermore, emerging professionals in the current study experienced difficulty managing stress and emotions, as well as financial burdens, as they pursued the profession. As shown in the current study and previous studies, stress can be related to completing the application (Reeves, 2019) or demonstrating in applications or interviews the traits clinical sites are looking for applicants to have including experience, developmental knowledge, and efficient communication skills (Sisk et al, 2023). Like previ-ous studies have shown, emerging professionals often look to social media for support and coping with the barriers to entering the profession (Hammond, 2021).…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Furthermore, emerging professionals in the current study experienced difficulty managing stress and emotions, as well as financial burdens, as they pursued the profession. As shown in the current study and previous studies, stress can be related to completing the application (Reeves, 2019) or demonstrating in applications or interviews the traits clinical sites are looking for applicants to have including experience, developmental knowledge, and efficient communication skills (Sisk et al, 2023). Like previ-ous studies have shown, emerging professionals often look to social media for support and coping with the barriers to entering the profession (Hammond, 2021).…”
Section: Discussionmentioning
confidence: 56%
“…Qualitatively, participants detailed specific elements of their academic and clinical experiences that impacted their levels of engagement, motivation to pursue child life, and feelings of burnout -all of which can be mapped onto concrete organizational and institutional systems improvements previously suggested (Adelson et al, 2022;Hammond, 2021;Jenkins et al, 2023;Sisk et al, 2023). When participants have access to accurate, comprehensive information, knowledgeable and supportive academic mentors with clinical child life experience, an extensive network of peer and personal support, and opportunities to garner direct exposure to the child life field, they can thrive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Historically, child life has been seen as a competitive profession and students often spend multiple semesters waiting to receive an internship position. Reportedly, child life internship coordinators often receive 50 to 100 applications from prospective internship students each application round, but despite the large number of students enrolled in child life academic programs, some hospitals do not fill their open internship positions (Sisk et al, 2023). When obtaining an internship position is so difficult, these un-filled positions are especially concerning.…”
Section: Child Life Internship Readiness: Perspectives Of Child Life ...mentioning
confidence: 99%